External root resorption of second molars caused by impacted third molars: an observational study in panoramic radiographs - LACERDA-SANTOS,Jhonatan Thiago (2018)
Abstract Objective This research investigate the presence of external root resorption (ERR) in second molars caused by impacted third molars in panoramic radiographs, relating to the position of third molars according to classification of Winter, Pell and Gregory. Material and method A cross-sectional, retrospective study using panoramic radiographs obtained from January 2014 to December 2015. The inclusion criterion was the presence of a second molar adjacent to an impacted third molar. Data were analyzed using descriptive and inferential statistics. Pearson's Chi-Square Test and Fisher's Exact Test (p≤0.05) were performed. Result The sample consisted of 584 panoramic radiographs, 356 (60.95%) of women, and 228 (39.05%) of men, the mean age was 25.31 years. The prevalence of ERR was 12.5%, and the group of 14-24 year olds was the most affected (p = 0.46). The presence of ERR was statistically higher in the mandible (42.1%) with p=0.01. The ERR located in the cervical (57.1%) and medium (58.8%) thirds was proportionally higher in the teeth with B2 (p=0.02) and mesio-angular positions (p=0.26). Conclusion The prevalence of ERR in second molars, caused by impacted third molars, was shown to be similar to results found in the literature, with no gender preference, this affects young patients, occurring frequently in mandible teeth, and presents greater severity in the cervical and middle thirds. The B2 and mesio-angular positions were more prone to ERR.